Loss of SHP-2 activity in CD4(+) T cells promotes melanoma progression and metastasis - Zhang, Tao (Nature Publishing Group, 2013)
The Src homology 2 domain-containing tyrosine phosphatase 2 (SHP-2) has been reported to have both tumor-promoting and tumor-suppressing roles in tumorigenesis. However, the role of SHP-2 in tumor immunity remains unclear. Here we observed progressively lower levels of phosphorylated SHP-2 in tumor-associated CD4(+) T cells during melanoma development in a murine model. Similarly, the levels of phosphorylated SHP-2 in the CD4(+) T cells of human melanoma specimens revealed a decrease paralleling cancer development. The CD4(+) T cell-specific deletion of SHP-2 promoted melanoma metastasis in mice. Furthermore, SHP-2 deficiency in CD4(+) T cells resulted in the increased release of inflammatory cytokines, especially IL-6, and the enhanced accumulation of tumor-promoting myeloid-derived suppressor cells (MDSCs) in tumor-bearing mice. An IL-6-neutralizing antibody reduced MDSC accumulation and inhibited tumor growth in CD4(+) T-cell-specific SHP-2-knockout mice. Our results suggest that SHP-2 in CD4(+) T cells plays an important role in preventing melanoma progression and metastasis.